Early Intervention in the Structure of Children's Rehabilitation (on the Example of the Republic of Tatarstan) - Darya L. Nefedeva; Rezeda A. Bodrova; Elena G. Ignashina; Ayrat I. Ziatdinov; Svetlana A. Senek (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2021)
The early intervention system is currently considered as an independent activity which has a clear conceptual model. The generalmechanisms of the early intervention system facilitate the child's social adaptation and its integration into the educational environment. This creates the conditions for the child development and the formation of the child's skills necessary in daily life situations. At the same time, it remains unclear how the routing of a child in need of rehabilitation is carried out, taking into account the need toreceive early intervention services for the target group of patients. Aim. To determine the place of early intervention in the structure of the rehabilitation service of the Republic of Tatarstan. Results and Discussion. The early intervention system contains functional, personality-oriented and environmental approaches,which are implemented using the domains of activity and participation of the International Classification of Functioning, Disabilitiesand Health. The use of this classification implies the need for joint work of the number of specialists who make up a multidisciplinaryteam, forms a unified methodology for constructing rehabilitation plans and early assistance programs, and offers a conceptual basisfor analyzing the effectiveness of their implementation. In addition, the application of the International Classification of Functioning,Disabilities and Health makes it possible to determine the role of early intervention when planning a child's rehabilitation route. The articlepresents a model of routing a child in need of rehabilitation measures, implemented in the Republic of Tatarstan, which providesfor early identification of children with indications and their referral accordingly to these indications to early intervention, medical orsocial rehabilitation. Conclusion. Identifying children of the target group in need of the early intervention and their timely referral to organizations that areproviders of relevant services is one of the stages in solving urgent problems of rehabilitation. Currently, the departments of early interventionsystem are opened on the basis of medical, social and educational organizations in the Republic of Tatarstan, and includedin the rehabilitation structure playing an important integrating role in the formation of interagency cooperation.